Raising Healthy Children: Food Allergies - Lauren Headrick; Karla P. Shelnutt; Gail P. A. Kauwell (EDIS)
If your child has a newly diagnosed food allergy, you may feel scared, confused, and anxious. You are not alone. According to the Centers for Disease Control and Prevention, over three million children under the age of 18 have food allergies, and this number is growing rapidly. Food allergies can be caused by many different foods. The symptoms range from a mild skin rash to serious breathing problems. This 4-page fact sheet highlights the causes and symptoms of an allergic reaction, as well as the steps to take if your child has been diagnosed with a food allergy. Also included are recipes and possible changes to your family’s diet that can help make mealtime easier. Written by Lauren Headrick, Karla P. Shelnutt, and Gail P. A. Kauwell, and published by the UF Department of Family, Youth and Community Sciences, March 2012.